Extract of Adenanthera pavonina L. seed reduces development of diabetic nephropathy in streptozotocin-induced diabetic rats - Ramdas Pandhare; Balakrishnan Sangameswaran (Mashhad University of Medical Sciences, 2012)
Objective: The aim of the present study was to investigate the renal protective effect of Adenanthera pavonina (A. pavonina) seed aqueous extract (APSAE), in streptozotocin (STZ)-induced diabetic rats. Materials and Methods: The renal protective effect of A. pavonina seed aqueous extract (APSAE) was studied in STZ-induced diabetic rats. APSAE (50, 100 and 200 mg/kg per day) was given daily to diabetic rats for 13 weeks. Blood glucose, serum parameters such as albumin, creatinine, total protein, urea, lipid profile, glycated haemoglobin (HbA1c), and urine parameters such as urine protein and albumin were examined. Kidney histopathology was also done. Results: After 13 weeks of treatment, in STZ-induced diabetic rats, severe hyperglycemia was developed, with marked increase in proteinuria and albuminuria. However, APSAE treatment significantly reduced proteinuria, albuminuria, lipid levels, and HbA1c deposition in diabetic rats. Conclusion: These results suggested that APSAE has reduced development of diabetic nephropathy in streptozotocin-induced diabetic rats and could have beneficial effect in reducing the progression of diabetic nephropathy.